Participación ciudadana, patrimonialistas y gestión del patrimonio cultural inmueble precolonial del Perú - Alexandrino Ocaña, Grace (2023)
For over ten years, Peru has seen the rise of groups of citizens who want to take over the responsibility for the safeguard[1]ing of the nation’s pre-colonial cultural heritage. Citizen participation in the safeguard of heritage has not been much implemented despite its inclusion in the legal regulations laid down by the Peruvian government. Even more, Peru’s authorities and cultural experts still favour a material-centred preservation outlook over the social use and the interac[1]tion between contemporary societies and the built heritage. Based on an extensive ethnographic and archival work, I here characterize what citizen participation in the management of pre-Colonial structures has been like since the estab[1]lishment of the Ministry of Culture; describe the way in which citizen participation has developed ever since cultural heritage grassroots organizations appeared; and discuss the potential that citizen participation holds for the attainment of a more sustainable management of heritage.